Investigating Online Fraud with the BRI Mobile Mode : Modus Operandi and the Gaps in Law Enforcement - Febriansyah Febriansyah; Musriko Musriko (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Cyber universe was made uproar by the actions of fraudsters posing as bank employees. Fake advertisements are a 'cover' for fraudsters in their efforts to 'drain' victims' money. In 2023, the South Jakarta District Court sentenced 9 perpetrators. this article, we will examine in depth the modus operandi used by the perpetrators, related to legal regulations. a critical assessment will be carried out regarding law enforcement carried out by the Public Prosecutor and the Panel of Judges. The author uses a legal research with statutory and regulatory policies and case approach to answer the problem. The results of the research show that the perpetrators used various modes, where each of these is an independent criminal act. It was found that there were gaps in the legal enforcement of this case, especially by the prosecutor, which included a lack of understanding regarding the ITE Law and other related regulations, as well as inconsistencies in the application of the concurus realis doctrin and sustainable actions, and there were indications of lack of seriousness in handling it, where Article 36 of the ITE Law which is the severity of punishment, is not applied in the indictment